Assessment of ICT tool usage in teaching Chemistry among secondary school teachers - Nafisat Oyebola Oyeniyi; Tawa Abiola Ahmed; Habibat Bolanle Abdulkareem (Universitas Pendidikan Indonesia, 2024)
The study explored the availability and utilization of ICT tools for chemistry teaching in Offa Local Government Area (LGA) of Kwara State. The study employed a descriptive survey research design. Purposive sampling was adopted to choose twenty-one chemistry teachers from sixteen public senior secondary schools and five private senior secondary schools in Offa LGA for the study. The tool employed to obtain the data was a questionnaire that the researcher designed. The instrument was face-validated by senior lecturers in scientific education and Pearson's Product Moment Correlation Coefficient (PPMC). The study found that the minimal ICT resources available were only moderately used to teach chemistry and that public and private schools in Offa LGA, Kwara State, have some ICT resources. It was suggested that the government give sufficient ICT resources to public schools and that private school owners supply sufficient ICT resources to their schools. It was also suggested that chemistry teachers use ICT resources when instructing Chemistry. Abstrak Penelitian ini meneliti ketersediaan dan pemanfaatan perangkat TIK untuk pengajaran kimia di Offa Local Government Area (LGA) di Negara Bagian Kwara. Penelitian ini menggunakan desain penelitian survei deskriptif. Pengambilan sampel secara sengaja dilakukan untuk memilih dua puluh satu guru kimia dari enam belas sekolah menengah atas negeri dan lima sekolah menengah atas swasta di Offa LGA untuk penelitian ini. Perangkat yang digunakan untuk memperoleh data adalah kuesioner yang dirancang oleh peneliti. Instrumen tersebut divalidasi oleh dosen senior dalam pendidikan sains dan Product Moment Correlation Coefficient (PPMC). Penelitian ini menemukan bahwa sumber daya TIK minimal yang tersedia hanya digunakan secara moderat untuk mengajar kimia dan bahwa sekolah negeri dan swasta di Offa LGA, Negara Bagian Kwara memiliki beberapa sumber daya TIK. Di antara hal-hal lain, disarankan agar pemerintah memberikan sumber daya TIK yang cukup untuk sekolah negeri dan agar pemilik sekolah swasta menyediakan sumber daya TIK yang cukup untuk sekolah mereka. Disarankan juga agar guru kimia memanfaatkan sumber daya TIK yang dapat diakses dengan baik saat mengajar Kimia. Kata Kunci: asesmen guru; guru kimia; pemanfaatan TIK; perangkat TIK